Effects of Current Density on Surface Morphology and Coating Thickness of Nickel Plating on Copper Surface (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nickel (Ni) thin film was deposited on commercial pure copper using electrodeposition method. To understand the growth behavior of Ni nodules, deposition was done by varying the coating current density. The topography of coating was analyzed using Scanning Electron Microscope (SEM). The coatings were also analyzed for variation in amount of coating, cathode current efficiency and thickness of coating. The deposited Ni thin film was observed to be of coffee bean kind of secondary nodules with size varying from 400 to 800 nm and almost spherical primary nodules with size varying from 100 to 250 nm varying as a function of coating current density. At higher current density, the coatings were observed to be of multiple layers of nodules. This suggests the presence of defects like twins, dislocations and stacking faults. The nodules are observed to have fine crystallites in the nano range.